2006
DOI: 10.1089/thy.2006.16.625
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the 258 A/G (D2-ORFa-Gly3Asp) Human Type-2 Deiodinase Polymorphism: A Naturally Occurring Variant Increases the Enzymatic Activity by Removing a Putative Repressor Site in the 5′ UTR of the Gene

Abstract: These data suggest that the increase in gene transcription induced by the 258A polymorphism could be mediated by reduction in the binding ability of a putative nuclear repressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“…The risk of MCI was decreased in male carriers of the Asp allele (OR = 0.471, P < 0.05). Examination of the relationship between different genotypes of ORFa-Gly3Asp and TH revealed that the serum level of T 3 in male carriers of the Asp allele was higher than that of Gly carriers, which was consistent with the results of Coppotelli et al (2006). Thus, the Gly3Asp mutation in males may increase the serum level of T 3 , decrease the incidence of MCI, and act as a protective factor.…”
Section: Discussionsupporting
confidence: 77%
“…The risk of MCI was decreased in male carriers of the Asp allele (OR = 0.471, P < 0.05). Examination of the relationship between different genotypes of ORFa-Gly3Asp and TH revealed that the serum level of T 3 in male carriers of the Asp allele was higher than that of Gly carriers, which was consistent with the results of Coppotelli et al (2006). Thus, the Gly3Asp mutation in males may increase the serum level of T 3 , decrease the incidence of MCI, and act as a protective factor.…”
Section: Discussionsupporting
confidence: 77%
“…Cells were homogenized in 0.25 M sucrose, 0.02 M Tris/HCl (pH 7.0), and 1 mM EDTA. After centrifugation at 1000 ϫ g, the supernatant was collected and stored at -80 C. De-iodinase activity was measured according to previously described methods (42,43). Each reaction was performed in the presence of 5 mM propylthiouracil (Sigma), an inhibitor of de-iodinase type 1.…”
Section: Molecular Modeling and Dockingmentioning
confidence: 99%
“…Previous studies have demonstrated that polymorphisms in the deiodinase genes might interfere in the phenotypic expression of these enzymes (6,10). Interestingly, a study described a single-nucleotide polymorphism in D2, in which a threonine (Thr) changes to alanine (Ala) at codon 92 (D2 Thr92Ala) was associated with w20% lower glucose disposal rate in nondiabetic subjects (11).…”
Section: Introductionmentioning
confidence: 99%